Redescription of Proteocephalus glanduligerus (Cestoda: Proteocephalidea), a parasite of clariid catfishes in Africa with a unique glandular apical organ - Scholz, Tomás; de Chambrier, Alain; Beletew, Moges; Mahmoud, Zuheir N (The Journal of parasitology, 2009)
The tapeworm Proteocephalus glanduligerus (Janicki, 1928) Fuhrmann, 1933 (Cestoda: Proteocephalidea), a parasite of clariid catfishes (Clarias spp.) in Africa, is redescribed on the basis of an evaluation of voucher material and newly collected specimens from Clarias gariepinus and C. cf. anguillaris from the Sudan, Ethiopia, and South Africa. The most typical characteristic of P. glanduligerus (previously misspelled as P. glanduligera or P. glanduliger) is the presence of an extremely large glandular apical organ, the size of which is 1.6-3.5 times larger than that of the suckers. In addition, other morphological characteristics unreported in previous accounts are provided, such as an unusual position of osmoregulatory canals (situated close to each other, with the dorsal canal latero-ventral to testes), the presence of a vaginal sphincter, several (usually 3-5) uterine pores, and eggs with paired lateral auricular swellings (extensions) of the outer envelope.
Keywords: Ethiopia; Cestoda; Súdán; Fish Diseases; cestodózy; zvířata; Jihoafrická republika; Catfishes; Sudan; Cestode Infections; nemoci ryb; Etiopie; řeky; Egypt; Rivers; South Africa; sumci; Animals